Supercyclic and Hypercyclic Generalized Weighted Backward Shifts over a Non-Archimedean <semantics>c0(N)</semantics> Space - Farrukh Mukhamedov (MDPI AG, 2021)
In the present paper, we propose to study generalized weighted backward shifts <semantics>BB</semantics> over non-Archimedean <semantics>c0(N)</semantics> spaces; here, <semantics>B=(bij)</semantics> is an upper triangular matrix with <semantics>supi,j|bij|<∞</semantics>. We investigate the sypercyclic and hypercyclic properties of <semantics>BB</semantics>. Furthermore, certain properties of the operator <semantics>I+BB</semantics> are studied as well. To establish the hypercyclic property of <semantics>I+BB</semantics> we have essentially used the non-Archimedeanity of the norm which leads to the difference between the real case.